Flexible Electronics Materials and Applications - Wong, William S.; Salleo, Alberto (Electronic Materials: Science & Technology ;, 2009)
Flexible Electronics: Materials and Applications surveys the materials systems and processes that are used to fabricate devices that can be employed in a wide variety of applications, including flexible flat-panel displays, medical image sensors, photovoltaics, and electronic paper. Materials discussed range from polymeric semiconductors to nanotube transparent conductors, and the important characteristics of each system and their target applications are highlighted. An overview of the performance benchmarks for the different materials is given in order to allow a direct comparison of these different technologies. Furthermore, the devices and processes most suitable for given applications in flexible electronics are identified. Topics include: An overview and history of flexible electronics Low-temperature processing and device integration on flexible substrates Solution-processable thin-film electronic devices and their properties Materials and device physics relevant to flexible electronics Mechanical and electrical characteristics of nano-scale materials on flexible platforms Printing and roll-to-roll processing for large-area electronics manufacturing Applications towards flexible displays, sensors, actuators, photovoltaics, radio-frequency identification, and micro-electro-mechanical systems Written by leading researchers in the field, Flexible Electronics: Materials and Applications serves as a reference for researchers, engineers, and students interested in the characteristics, capabilities, and limitations of these exciting materials and emerging applications.